Comparison between different papillary recession classification systems - Li-Ching Chang (Elsevier, 2012)
Background/purpose: Traditional classification systems to assess interdental papillary levels are based only on the vertical relationship among the papilla tip, contact point, and cementoenamel junction. However, the width of papilla recession (PR) is highly visible in terms of dental esthetics. A new classification system is presented to assess central PR and compare differences between the new system and existing systems. Materials and methods: Thecentral papillawas visually assessed in 450 adults using standardized periapical radiographs of the maxillary central incisors. The PR classification system presented here is based on vertical and horizontal dimensions of the PR area. Central PR was classified according to the PR system and the system of Nordland and Tarnow (TC). Results: Ninety individuals who had no PRs were classified as degree 0 according to the classification of both TC and Chang. A total of 330 individuals (73.3%) were classified as TC I (Tarnow), and 46, 89, 16, and 183 participants were classified as PR I, PR II, PR III, and PR IV (Chang). Thirty individuals were classified as TC II, and all were classified as PR IV. Conclusion: This study confirmed a significant correlation between the two existing classification methods. The proposed PR classification system characterizes open embrasures in greater detail than previous systems.